The Impact of ABO Blood Grouping on COVID-19 Vulnerability and Seriousness: A Retrospective Cross-Sectional Controlled Study among the Arab Community - El-Shitany, Nagla A.; El-Hamamsy, Manal; Alahmadi, Ahlam A.; Eid, Basma G.; Neamatallah, Thikryat; Almukadi, Haifa S.; Arab, Rana A.; Faddladdeen, Khadija A.; Al-Sulami, Khayria A.; Bahshwan, Safia M.; Ali, Soad S.; Harakeh, Steve; et al. (International journal of environmental research and public health, 2021)
Background and Objectives: Studies have noted that some ABO blood types are more susceptible to COVID-19 virus infection. This study aimed to further confirm the relationship between different blood groups on the vulnerability, symptoms, cure period, and severity among COVID-19 recovered patients. Subjects and Methods: This cross-sectional study approached the participants from the Arab community via social media (mainly Facebook and WhatsApp). The data were collected through two Google Form questionnaires, one for COVID-19 recovered patients (COVID-19 group, n = 726), and the other for the healthy people (Control group, n = 707). Results: The subjects with blood group O were the least likely to be infected with the COVID-19 virus, while those with blood group A were not likely to be the most susceptible. There were significant differences among different ABO blood groups regarding the distribution of oxygen saturation percentage, myalgia, and recovery time after COVID-19 infection (p < 0.01, 0.01, and 0.05, respectively). The blood group A showed the highest percentage of patients who experienced an oxygen saturation range of 90–100%, whereas the blood group O showed the highest percentage of patients who experienced an oxygen saturation range of 70–80%. The blood group A showed the lowest percentage of patients who required artificial respiration, whereas the blood group O showed the highest percentage of patients who required artificial respiration. The blood group B showed the lowest percentage of patients who experienced myalgia and exhibited the lowest percentage of patients who needed 3 weeks or more to recover. Conclusion: The people of blood group O may be the least likely to be infected with COVID-19, however, they may be the more in need of treatment in hospital and artificial respiration compared to the other blood groups.